Simulation of the Polymer Matrix Composite Reinforced by Metal Fiber - Kehlol, Kadim Khayoun (Nahrain University College of Engineering Journal, 2014)
In this search we simulate the polymer matrix composite of (epoxy) reinforcedwith wire of high carbon steel (Steel Reinforced Plastic) undulating and another withbend on the end and characterized of these wires by stiffness and toughness with lowcost. Study was that the mechanical properties of the composite material(tensile/compression) by a program (COMSOL Multiphysics ?.?).